Four new species of the genus Pseudopoda Jäger, 2000 (Araneae, Sparassidae) from Yunnan Province, China - Zhang, Bao-Shi; Zhang, Feng; Zhang, Zhi-Sheng (Zootaxa, 2013)
Four new species of the huntsman spider genus Pseudopoda Jäger, 2000 are reported from Yunnan Province, China: Pseudopoda gibberosa sp. nov. (male, female), P. semiannulata sp. nov. (male, female), P. breviducta sp. nov. (male, female) and P. triangula sp. nov. (male, female).